Phyto-Sociological Study of Hemlock (Tsuga dumosa) forest from Uttarakhand, India - Naithani, H. B. (Indian Forester, 2018)
Tsuga Dumosa, Most Westerly Extension Towards Munsiyari And Dharchula Ranges, Pithoragarh Forest Division. Vegetational Analysis For Its Associated Density, Frequency And Abundance Has Been Mentioned.